Properties study of ZnO：Ga crystal on pulsed radiation detections - 马彦良 欧阳晓平 张景文 张忠兵 潘洪波 陈亮 刘林月 (Chinese physics C, 2010)
In this paper, properties on pulsed radiation detections of ZnO：Ga crystal grew by a magnetron sputtering method were studied. The time response to pulsed laser, pulsed hard X rays and single α particles, the energy response to pulsed hard X ray, the scintillation efficiency to γ rays, the response to pulsed proton, and the relations of the light intensity varied with the proton energy were measured and analyzed in detail. Results show that the ZnO：Ga crystal has potential applications in the regime of pulse radiation detection.